2008
DOI: 10.1111/j.1467-9671.2008.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Student Performance in Online and Blended Sections of a GIS Programming Class

Abstract: Educators and non-educators alike commonly assume that online courses cannot match the effectiveness of their traditional, face-to-face counterparts. This article describes a comparative study of the performance and study habits of two groups of students in a course in Geographic Information Systems (GIS) software programming and customization: one delivered online to adult professionals working asynchronously; the other delivered in a blended, online/face-to-face environment to upper-level undergraduates in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Confounding issues regarding age distribution, gender, laboratory completion on-campus, and the possibility that online learners are better learners due to self-selection make this conclusion less easy to draw. These conclusions are supported by Detwiler's (2008) study of GIS students, where he found online students to demonstrate high self-motivation and maturity. Fowler (2005) asks, "Are on-site courses as effective as online?"…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Confounding issues regarding age distribution, gender, laboratory completion on-campus, and the possibility that online learners are better learners due to self-selection make this conclusion less easy to draw. These conclusions are supported by Detwiler's (2008) study of GIS students, where he found online students to demonstrate high self-motivation and maturity. Fowler (2005) asks, "Are on-site courses as effective as online?"…”
Section: Discussionsupporting
confidence: 66%
“…Detwiler (2008), in a comparison of a computer lab-based online and a blended face-to-face/online GIS class, found that online students outperformed face-to-face students. A survey of the study habits of these students pointed to maturity, time management, and ability to self-motivate as larger success factors than delivery mode.…”
mentioning
confidence: 97%
“…While the above studies indicate no difference in achievement between online and hybrid instruction, Detwiler (2008) discovered that an undergraduate cohort who took a GIS programming course in the hybrid format underperformed compared to the students who took the class completely online. This grand canyon university was one of the first studies that also examined student study habits between sections by having students keep a diary of the amount of time dedicated to the class.…”
Section: Comparison Of the Impact Of Hybrid Instruction Versus Onlinementioning
confidence: 90%
“…However, it should be mentioned that a few of the studies used inadequate testing methods and did not keep variables consistent for accurate data. For example, Detwiler (2008) used different populations of students, with adult, working professionals participating in the online format and undergraduate students in residence taking the hybrid class. While the authors examined student diaries to obtain information on motivation, the classes should have been compared with the same population of students for more accurate data.…”
Section: Comparison Of the Impact Of Hybrid Instruction Versus Onlinementioning
confidence: 99%
“…The results showed that the online cohorts significantly outperformed the face-to-face cohort in skill development; this was earned without any exposure to a face-to-face lecture or lab time. 29 Finally, another study (and one of the most interesting I read) sought to determine whether critical thinking skills could be effectively taught using the Web. Three groups were part of the study: Group 1 was a faceto-face class; Group 2 included regular face-to-face meetings, along with a series of critical thinking questions located online; and Group 3 had class lectures, readings and assignments via online only-no face-to-face contact.…”
Section: Skillsmentioning
confidence: 99%